Assessing real-world safety of plecanatide: a pharmacovigilance study based on the FDA adverse event reporting system - Zhang, Zhiyuan; Yao, Yifan; Zhu, Li (Frontiers in Pharmacology, 2024)
Background: Plecanatide is a selective gastrointestinal peptide used for the treatment of chronic idiopathic constipation (CIC) and irritable bowel syndrome with constipation (IBS-C). Given its widespread use, understanding the long-term safety of plecanatide in real-world settings is essential.Methods: Data for this study were sourced from the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from the first quarter of 2017 to the second quarter of 2024. Disproportionality analysis methods were employed to quantify adverse event signals associated with plecanatide. Additionally, a Weibull distribution analysis was conducted to assess changes in adverse events over time. Sensitivity analyses were performed to enhance the robustness of the findings.Results: A total of 861 cases associated with plecanatide were identified, including 2057 adverse event reports. Common positive adverse events included diarrhea, constipation, abdominal distension, dissatisfaction with treatment, rectal tenesmus, increased fecal volume, abnormal gastrointestinal sounds, and gastrointestinal motility disorders. The majority of adverse events related to plecanatide occurred within the first seven days of treatment. Findings were consistent across sensitivity analyses.This study preliminarily explores the safety of plecanatide in real-world applications, revealing significant new adverse event signals. These findings provide important safety references for clinicians prescribing plecanatide for CIC and IBS-C.